A Study on Product Factors Affecting Purchase Intention of Properties in Beijing - Zhang, Lijuan (2013)
The property market of Beijing becomes more and more remarkable in the eyes of Chinese and the world people. As the capital of China and the first-tier city, a higher purchase demands exit in Beijing property market. With the improvement of people’s living standards, they have desire to possess an own property or improve the living environment, it promote demands and requirements for housing quantity and quality are increasing. But the factors which affect purchase intention of properties are debatable. Therefore, the SOR model as a ‘theoretical lens’ is used in this study as it allows the product factors influencing purchase intention which can help the author to build an researchable expansion model. This research aims to find out the purchase intention of properties in Beijing. Based on the literature review that was available, a framework was developed and this research paper uses a quantitative method whereby 210 respondents were surveyed using questionnaires. The data was analyzed using the Statistical Package for Social Science (SPSS). The empirical results suggest that willingness to pay is a significant moderator between product factors and purchase intention. The findings also showed that product attributes will generate willingness to pay and further promoting purchase intention, then contributing to developers in designing properties in future.